Chunhyang, chunhyang, chunhyang: Poetics of Im Kwan-Taek's Chunhyang. Issue 1 (1st March 2002) - Choi, Jinhee
Im Kwan-Taek, a leading Korean director, explores an aspect of Korean artistic heritage, pansori, in his recent film Chunhyang (2000). Korean traditions influenced by Buddhism and Shamanism have been major themes in his other films, including Mandala (1981), Aje Aje Bara Aje (1989), and Daughter of the Flame (1983). In his film Chunhyang, Im combines two different art forms: the Korean traditional performance art pansori and cinema. Pansori was a major theme in his film, Sopyonje (1993), in which he portrays the life of the pansori performer Song-hwa, whose father sacrificed her sight for the sake of mastering the artistry of pansori. In an interview, Im tells us that without having made Sopyonuje, Chunhyang could not have come to existence.1 Unlike Sopyonje in which pansori is incorporated within the film through the characters' performances, in Chunhyang, pansori singing leads the narrative.